The Influence Of The Number Of Tourist Visits, The Number Of Tourist Attractions, And Local Levies On Local Revenue In The Perspective Of Islamic Economics (Study in South Sumatra province in 2014 – 2023) - Lestariza, Tri; Bahtiar, Muhammad Yusuf; Zulaikah (Cattleya Darmaya Fortuna, 2025)
South Sumatra province has great potential resources that can be developed. The contribution of local revenue can also come from the number of tourist visits, the number of tourist attractions, and regional levies. The phenomenon that occurred in South Sumatra province, there was a decrease in local revenue (PAD), the number of tourist visits, and the amount of regional levies during the Covid-19 pandemic. However, the number of attractions in South Sumatra province has increased. This study aims to assess the effect of the number of tourist visits, the number of tourist attractions, and local levies on local revenue (PAD) in the perspective of Islamic Economics in South Sumatra province in 2014-2023. This study includes quantitative research. The results showed that the number of attractions affect the local revenue (PAD) of South Sumatra province. While the number of tourist visits and local levies on local revenue (PAD) does not affect the local revenue (PAD) of South Sumatra province. Fiscal policy in Islam carried out by the government aims to create economic stability high economic growth rate and equitable distribution of income as stated in QS. See also verse 188.